The effect of using alternative LPG gas fuel on efficiency and exhaust emissions on Honda Astrea motorbikes - ahmad sulaiman; Anggara Sukma Ardiyanta; Emdi Ramadana Putra (Journal of Automotive Vocational Education (JAVED), 2025)
The rapid growth of motorized vehicles in urban areas, including Tulungagung, has become one of the main contributors to worsening air pollution. Emissions from the transportation sector account for approximately 71% of urban air pollution, surpassing contributions from industrial and household sectors. In addition to environmental concerns, the rising cost of fuel and incidents of fuel adulteration have highlighted the need for alternative, more economical, and environmentally friendly fuels. One such alternative is LPG (Liquefied Petroleum Gas), which has a higher octane rating (RON 112) compared to Pertalite (RON 90) and potential to reduce exhaust emissions. This study aims to determine the effect of using LPG fuel on fuel efficiency and exhaust emissions of a Honda Astrea Star motorcycle. The test was conducted by comparing fuel consumption and the content of CO, CO₂, and HC emissions between LPG and Pertalite fuels. The results showed that the use of LPG resulted in a fuel efficiency of 0.01923 l/km, slightly lower than Pertalite at 0.01925 l/km. In terms of exhaust emissions, LPG significantly reduced CO and CO₂ ,but HC emissions increased due to incomplete combustion, influenced by the conventional carburetor system and suboptimal LPG converter kit usage. In conclusion, although LPG has not been proven to significantly improve fuel efficiency in l/km units, this fuel can reduce certain exhaust pollutants, particularly CO and CO₂. Therefore, LPG has potential as an economical alternative fuel.